La rentabilidad mediante el uso de criptomonedas a través de un videojuego basado en tecnología blockchain - Cam Flores, Adrián Andrés (2023)
The purpose of this research is to review and determine the profitability generated by the investment of cryptocurrencies in the Video Game Based on Blockchain Technology (VBTB) application. In that line, it seeks to determine the various factors that affect the desired profits and how is the nature of the Smooth Love Potion (SLP) cryptocurrency. VBTB is a video game/app developed by Sky Mavis studio and, to start playing, one must purchase and form a team of 3 Axies. Each of these creatures is a Non-Fungible Token (NFT), a cryptographic asset or token that through blockchain technology allows you to create a unique asset that does not change. The cost of each Axie (game creature for online combat) varies and depends on various factors such as the characteristics of the Axie, its degree of competitiveness in the application, the cryptocurrency market in general that directly impacts VBTB and the modifications that the Sky Mavis studio decides to make to VBTB, becoming volatile in different scenarios. For the present investigation, the exploratory research methodology was adopted, with primary data, with a quantitative approach and a hypothetical-deductive method. Making use of the infinite type sample, it was obtained that the optimal number of users would be 384, through the closed survey instrument. The results obtained through the investigation highlight that profitability through VBTB is possible, if certain factors such as level of domain, operability and decision making that must be managed are met. In addition, the research establishes that VBTB is an investment alternative to consider in the financial market; considering that users diversify their investments, but taking into account that the main limitation of cryptocurrencies and the applications that use them are the volatility of their prices, being a very unstable investment alternative.